Daring to dream: reactions to tobacco endgame ideas among policy-makers, media and public health practitioners - Wilson Nick; Thomson George; Russell Marie; Edwards Richard; Gifford Heather (BMC, 2011)
Abstract Background Tobacco control strategies have mainly targeted reducing demand. Supply-side focused measures, though less familiar, deserve consideration, particularly to achieve 'endgame' tobacco control aims (e.g. achieving close to zero smoking prevalence). We explored attitudes towards supply-side focused 'endgame' tobacco control approaches and how they can be best communicated with senior policymakers, journalists, and public health practitioners. Methods We identified five supply-side focused approaches which could potentially lead to the tobacco endgame: two structural models and three discrete actions. The structural models were: (i) a Nicotine Authority to coordinate tobacco control activities and regulate the nicotine/tobacco market for public health aims; and (ii) a Tobacco Supply Agency acting as a monopoly purchaser of tobacco products and controlling the tobacco supply for public health aims. The actions were: (a) allocating progressively reducing tobacco product import quotas (the 'sinking lid') until importation and commercial sale of tobacco products ceased; (b) making tobacco companies responsible for reducing smoking prevalence with stringent financial penalties if targets were missed; and (c) new laws to facilitate litigation against tobacco companies. These approaches were presented as means to achieve a tobacco free New Zealand by 2020 to 19 senior policymakers, journalists, and public health physicians in two focus groups and eight interviews, and their reactions sought. Results The tobacco-free vision was widely supported. Participants engaged fully with the proposed tobacco control approaches, which were viewed as interesting or even intriguing. Most supported increasing the focus on supply-side measures. Views differed greatly about the desirability, feasibility and likely effectiveness of each approach. Participants identified a range of potential barriers to implementation and challenges to successfully advocating and communicating these approaches. The current framing of tobacco as a risky but legal commodity was noted as an important potential barrier to implementing endgame approaches. Conclusions Endgame tobacco control approaches were considered to be viable policy options. Further policy analysis, research and public discussion are needed to develop endgame approaches. A significant change in the public framing of tobacco may be a prerequisite for implementing endgame solutions.